A MEASUREMENT MODEL OF SUCCESSFULL HALAL INDUSTRY - Efri Syamsul Bahri; Juhary Ali (UIN Mataram, 2022)
The halal industry has experienced accelerated growth globally, contributing RM7.4 trillion (USD 2.3 trillion). Therefore, this study proposes a conceptual model of the halal industry’s success within a literature review, including a descriptive-qualitative approach. It is utilised to define the indicators concerning the success of the halal industry and predictor factors that have a significant effect. This study is a conceptual work that identifies several factors that influence the success of the halal industry by surveying several factors that affect them. The survey was performed through a literature review. This study displays three indicators of success in the halal sector: business growth, growth, the decision to buy, and financial performance. In addition, this study discovered that four factors are predicted to significantly affect the success of the halal industry: halal certification, product quality, governance support, and Sharia banks. The results obtained from conceptual models and hypotheses are demanded to examine this effect. It is also utilised to design new constructions validated to confirm the halal industry in various countries. Therefore, this conceptual model stands desired to study the success of specific halal sectors further